(untitled) (Proceedings of International Educators Conference, 2024)
This work investigated the effect of a substitute for natural fructose sugar on the level of glucose and insulin in the blood serum in rats. It was found that the administration of fructose to animals for 30 days at a dose of 600 mg/kg orally leads to an increase in the amount of glucose and insulin in the blood, as well as to increased development of insulin resistance. The results obtained using fructose, a natural sugar substitute, showed results similar to those in type 2 diabetes.